Coexistence of Misconceptions and Scientific Conceptions in Chemistry Professors: A Mental Chronometry and fMRI Study - Patrice Potvin; Guillaume Malenfant-Robichaud; Caroline Cormier; Steve Masson (Frontiers in Education, 2020)
Using mental chronometry and functional magnetic resonance imaging (fMRI), 17 pre-university and university professors were tested with a cognitive task that required distinction of true or false statements about chemistry. These were prepared in pairs of similar statements, which differed only by congruency: while congruent stimuli involved no plausible interference of misconceptions, the incongruent match did. Results show longer response times and more activation in brain areas related to inhibitory control for incongruent compared to congruent statements, thereby supporting the hypothesis that misconceptions interfere in the production of scientific answers, even by experts. Possible educational implications are discussed.